Promoting communicating in yoruba language among young people in south west, nigeria (2017)
A body of linguists committed to preservation of languages claimed that about half of the world’s languages are endangered. Among these endangered languages is the Yoruba language, one of Nigeria’s major languages. Highlighting the importance of language as a form of cultural transmission, identification and socialization, the paper explores how globalization is endangering indigenous languages especially Yoruba language. The paper further explores possible challenges such as rural urban drift, adoption of English as language of communication, media propagation of English compared to Yoruba, Anglicization of indigenous names among youths and attitudes of elites to Yoruba speakers that could contribute to obstacle to speaking Yoruba language among young people in South West, Nigeria. Nevertheless, the paper states the need for the creation of awareness on Yoruba language among young people. Also, it calls for the need to encourage youth to speak Yoruba language, revive the storytelling tradition, promote cultural values among young people, promote Yoruba programmes in the broadcast media in order to discourage the use of code switching during communication among young people. Hence, there is a need for re-orientation of youths and other members of the society to make them cherish Yoruba language while the government should intensify the teaching of Yoruba language as compulsory subject in both primary and secondary schools in South West, Nigeria.